Exploring political environment and national culture impact on internationalization readiness of SMEs / Herwina Rosnan and Nuraisyah Chua Abdullah. - Rosnan, Herwina; Chua Abdullah, Nuraisyah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
The purpose of this study is to examine the influence of Political Environment and National Culture on Internationalization Readiness. The Smart-Partial Least Squares (PLS) analysis was used as to investigate the research model based on the survey of 60 Small and Medium-sized Enterprises (SMEs) from various industries which include companies in pharmaceutical, technological, electronic and foods and beverages in Klang Valley, Malaysia. The results supported the effects of two exogenous variables toward endogenous variable (Internationalization Readiness). Since the samples were limited to some SME companies in Klang Valley, Malaysia, the results of this study can only achieve theoretical generalization. Statistically, this study may prove not to be generalizable to the sample and should be confirmed using larger samples.